A construção da imagem dos imperadores Galba, Otão e Vitélio por Tácito e Plutarco - Ceola, Adriele Andrade (2017)
Historical narrative and biography are very old writing models, and from their very beginnings have shown similarities in their composition and content, although they have always been known as different genres. When we focus on Cornelius Tacitus' historical narrative Histories and Lucius Mestrius Plutarch's biographies, in particular Life of Galba and Life of Otho amidst the Parallel Lives, we find a likesome concern in regards to the testimonies. Tacitus (54-120 a.D) was a historian par excellence, an aristocrat of provincial origin who held legal positions of the imperial judiciary several times; Plutarch (45-127 a.D), also of aristocratic origin, was from Chaeronaea, and was also known for his classes and lectures among the notable Romans, along with records that he exercised political offices in his homeland. Both were contemporaries and wrote about the emperors Galba, Otho and Vitellius, rulers between the years of 68 and 69 a.D. Therefore, this paper seeks to understand the construction of image of emperors of civil wars from 68-69 a.D, based on the tacitecian and plutharchian writings